Haematological and biochemical parameters during the laying period in common pheasant hens housed in enhanced cages - Hrabčáková, Petra; Voslářová, Eva; Bedáňová, Iveta; Pištěková, Vladimíra; Chloupek, Jan; Večerek, Vladimír (TheScientificWorldJournal, 2014)
The development of selected haematological and biochemical parameters during the laying period was monitored in common pheasant hens housed in an enhanced cage system. The cages were enhanced by the addition of two perches and a shelter formed by strips of cloth hanging in the corner of the cage. The results showed significant changes in the haematological and biochemical parameters monitored during egg laying. At the time when laying capacity approached a maximum, a decrease was observed (P < 0.05) in haematocrit, erythrocytes, and haemoglobin values, whereas monocytes, eosinophils, the heterophil/lymphocyte ratio, phosphorus, and calcium exhibited an increase (P < 0.05). At the end of the laying period, an increase (P < 0.05) was recorded in the count of leukocytes, heterophils, lymphocytes and basophils, the heterophil to lymphocyte ratio, and the concentrations of aspartate aminotransferase, cholesterol, phosphorus, and calcium, whereas lower values (P < 0.05) were recorded for haematocrit and plasma total protein in comparison with the values of the indicators at the beginning of the laying period. The results provide new information about dynamic changes in selected haematological and biochemical parameters in clinically healthy common pheasant hens during the laying period.
Keywords: krevní obraz; Analysis of Variance; Animals; Aspartate Aminotransferases; cholesterol; Female; kladení vajíček; ženské pohlaví; fosfor; erytrocyty; vápník; Cholesterol; Hematocrit; Oviposition; Galliformes; analýza rozptylu; Animals, Domestic; aspartátaminotransferasy; Calcium; Erythrocytes; Hemoglobins; Czech Republic; Housing, Animal; Phosphorus; Česká republika; hemoglobiny; hospodářská zvířata; zvířata; hematokrit; bydlení zvířat; Blood Cell Count